POTRET SIKAP RADIKALISME MENUJU PADA PERILAKU TERORISME DI KABUPATEN LAMONGAN - Ahmad Sholikin (Universitas Sultan Ageng Tirtayasa, 2018)
This research portrays religious attitudes of radicalism and terrorism which are manifested in the prohibition of religious worship activities, the spread of hatred, religious based violence or destruction of places of worship. This study uses a grounded theory research design. This research took place in Lamongan because the city was known as a region with religious schools laying out terrorist actors in Indonesia. The scientific contribution of this research is as a warning to the government to always be aware of radical and terrorist acts. This research describes a person's behavior from radicalism to terrorism is influenced by several factors, including differences in beliefs, ethnicity, socio-economic status as an initial symptom that has the potential to produce symptoms of radicalism to terrorism. But this difference if it is not supported by the existence of economic interests that play a role in linking the differences with radicalism and terrorism which, if strengthened later can also produce terrorism. On the other hand there is the role of the presence of the state, which can reduce or strengthen the role of economic interests in generating radicalism and terrorism.